(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to examine the relationships among evaluation of green credit card services, overall satisfaction with green credit card services, and loyalty to green credit cards. In addition, this search examines whether consumers’ green ethics moderates the relationship between evaluation of green credit card services and loyalty to green credit cards. An online survey (N = 2,000) was conducted to test the hypotheses. Consistent with all the hypotheses, the results indicate that (1) evaluation of green credit card services has a positive effect on overall satisfaction with green credit card services (hypothesis 1); (2) evaluation of green credit card services has a positive effect on loyalty to green credit cards (hypothesis 2); (3) overall satisfaction with green credit card services has a positive effect on loyalty to green credit cards (hypothesis 3); (4) overall satisfaction with green credit card services mediates the relationship between evaluation of green credit card services and loyalty to green credit cards (hypothesis 4); and (5) the magnitude of the positive effect of evaluation of green credit card services on loyalty to green credit cards increases as individuals’ green ethics decreases (hypothesis 5).